1985
DOI: 10.1111/j.1467-8470.1985.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in suspended sediment concentration during storms in five small catchments in southeast New South Wales

Abstract: Suspended sediment concentrations were determined during storm events for five small catchments in the Wallagaraugh River in southeast New South Wales between July 1977 and June 1978. A total of thirty‐nine storm responses were analysed and both storm hydrographs and hysteresis loops were produced. The behaviour of suspended sediment concentration was extremely variable and seven different types of response were recognised. In these catchments there is no simple single constant relationship between discharge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 3 publications
2
35
2
1
Order By: Relevance
“…At the catchment scale, the most important link occurs between the hillslope and stream channel. Several studies have reported an increase in sediment yield immediately following logging, indicating that the hillslope and drainage system are indeed connected (Fredriksen, 1970;Graynoth, 1979;Anderson and Potts, 1987;Cornish and Binns, 1987;Olive and Rieger, 1987;Harr et al, 1988). Much of the soil movement by hillslope processes, however, appears to be dominated by deposition on slopes rather than direct delivery to streams (Swanson and Fredriksen, 1982).…”
Section: Sediment Sources and Deliverymentioning
confidence: 92%
“…At the catchment scale, the most important link occurs between the hillslope and stream channel. Several studies have reported an increase in sediment yield immediately following logging, indicating that the hillslope and drainage system are indeed connected (Fredriksen, 1970;Graynoth, 1979;Anderson and Potts, 1987;Cornish and Binns, 1987;Olive and Rieger, 1987;Harr et al, 1988). Much of the soil movement by hillslope processes, however, appears to be dominated by deposition on slopes rather than direct delivery to streams (Swanson and Fredriksen, 1982).…”
Section: Sediment Sources and Deliverymentioning
confidence: 92%
“…Dominant vegetation is silvertop ash with stringybarks being common . Mean annual rainfall is in the order of 900-1000 mm, but is extremely variable (Olive & Rieger, 1985) . Storm runoff sediment concentration rarely exceeds 100 mg 1 -' in undisturbed catchment areas (Olive & Rieger, 1985) .…”
Section: Turbidity In Geebung Creek Catchmentmentioning
confidence: 99%
“…Olive & Rieger, 1985). An explanatory approach to stream sediment modelling thus requires accurate characterisation of the trend in concentration over time (Finlayson, 1985) .…”
Section: Introductionmentioning
confidence: 99%
“…We have attempted to link flow and sediment-supply conditions to predictable hydrometeorological events as a step toward development of a forecast model for large sediment-transport events. Piest et al, 1975Wood, 1977O'Loughlin et al, 1978Paustian and Beschta, 1979Doty et al, 1981Carling, 1983Olive and Rieger, 1985Sidle and Campbell, 1985 width of loop dependent upon degree of depletion. Bryan and Campbell, 1986Anderson and Potts, 1987Tassone, 1987Williams, 1989Smith and Olyphant, 1994Slattery and Burt, 1996 Alta Gully sidewalls are unstable in the deeply incised middle section ( Figure 3b).…”
Section: Introductionmentioning
confidence: 97%